SCIENTIFIC-THEORETICAL BASIS OF DIDACTIC-METHODICAL POSSIBILITIES IN ENSURING CONTINUITY OF PRESCHOOL AND PRIMARY EDUCATION - Sharipova Hanifa Alisherovna (Journals Park Publishing, 2023)
In this thesis, the ideas about interactive methods and their importance, the origin of the methods and their authors, and their effectiveness, used in the process of lessons and training with primary school students and preschoolers are put forward.
Keywords: pedagogue, interactive method